Relationship between BCA TBK KCP Tidar Surabaya Customer Service Communication Style and Customer Service Satisfaction - Veronika Imanuel Puraji; Anita Agustina Wulandari (DIGICOM : Jurnal Komunikasi dan Media, 2023)
This research is a study that examines the influence of the communication style of BCA customer service Tidar sub-branch offices on the level of customer satisfaction. research uses quantitative methods, quantitative methods are defined as research methods used to examine certain populations or samples, data collection uses research instruments, data analysis is quantitative statistics, with the aim of testing the hypotheses that have been set. This study collected data by filling out the Google form technique. In providing satisfaction to BCA customers, customer service is the spearhead in serving customer complaints. Communication between customer service and customers is one of the important factors that can influence a customer's assessment of BCA. Interpersonal communication is one of the customer service efforts to achieve customer satisfaction. The results of this study indicate that there is a relationship between the two variables which is considered very strong, the conclusion is based on the correlation table used as an indicator of the strength and weakness between the two variables. It can also be concluded that the hypothesis is accepted, namely that there is a significant influence of the communication style of BCA Tbk customer service at the Tidar Surabaya Sub-Branch Office on the level of customer service satisfaction.